2018
DOI: 10.4102/sajems.v21i1.1966
|View full text |Cite
|
Sign up to set email alerts
|

The link between Internet investor relations and information asymmetry

Abstract: Background: Information asymmetry manifests when one party has more or better information than the other. Information asymmetry is said not only to increase transaction costs and decrease liquidity, but also to diminish the quality of the investment decisions taken by investors, thus weakening the overall functioning of markets. Aim and setting: A well-developed Internet investor relations (IIR) strategy, coupled with increased disclosure levels, should theoretically decrease information asymmetry levels. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
(87 reference statements)
0
6
0
1
Order By: Relevance
“…Other studies have found a negative and statistically significant association between internet based disclosure and information asymmetry. This is the case of the studies of Pour and Imanzadeh (2017) in Iran; DaSiva Rodrigues and Caio Galdi (2017) in Brazil; Nel et al (2018) in South Africa. These studies concluded that the voluntary dissemination of information on the web site improves the company’s visibility and consequently decreases information asymmetry.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 95%
“…Other studies have found a negative and statistically significant association between internet based disclosure and information asymmetry. This is the case of the studies of Pour and Imanzadeh (2017) in Iran; DaSiva Rodrigues and Caio Galdi (2017) in Brazil; Nel et al (2018) in South Africa. These studies concluded that the voluntary dissemination of information on the web site improves the company’s visibility and consequently decreases information asymmetry.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 95%
“…Nel & Brummer (2016) designed a methodic, which allows to measure IR strategy and its effectiveness, was proved by assessment of the listed companies. Then they continue to research IR issues (Nel, Smit and Brummer, 2018) and confirm that there is a correlation between well-designed Internet IR strategy and decreasing of financial asymmetry. Later, the scientists considering the data of the Johannesburg Stock Exchange reveal the correlation between implemented IR Strategy and the cost of capital (Nel, Smit and Brummer, 2019).…”
Section: Literature Reviewmentioning
confidence: 88%
“…Corporate disclosures affect information asymmetry (Ajina, Sougne, & Lakhal, 2015). Nel, Smit, and Brummer (2018) found a significant negative association between disclosure vehicles in the annual report and information asymmetry. Thus, it could be concluded that corporate governance was negatively associated with financial information asymmetry.…”
Section: Corporate Governancementioning
confidence: 99%
“…Hence, the parent company must only motivate subordinates to work following the parent company policy to prevent corruption in the organization. Nel, Smit, and Brummer (2018) indicated that information asymmetry manifests when one party has more information than the other.…”
Section: Financial Information Asymmetrymentioning
confidence: 99%